Take me home protecting America's vulnerable children and families - Berrick, Jill Duerr (Oxford : Oxford University Press, 2009)
There is a profound crisis in the United States' foster care system, Jill Duerr Berrick writes. No state has passed the federally mandated Child and Family Service Review; two-thirds of the state systems have faced class-action lawsuits demanding change; well over half of all children who enter foster care never go home.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Foster home care -- United States; Foster children -- United States; Child welfare -- United States